The nexus of business sustainability and organizational learning: A systematic literature review to identify key learning principles for business transformation - Verena Hermelingmeier; Timo von Wirth (Business Strategy and the Environment, 2021)
Companies play a central role in the quest for sustainable development. Organizational learning theories have been utilized to explain sustainability-related change processes in firms. However, implications from studies at the nexus of business sustainability and organizational learning are highly dependent on varying conceptualizations. The objective of this study is to provide clarity on the plurality of conceptual underpinnings in research and to uncover principles that are associated with deeper organizational change processes, that is, business transformation. Building on insights from a systematic literature review, we develop a sustainability learning typology, from which we distill three learning principles for business transformation: (1) the deutero learning mode, (2) the societal learning scope, and (3) the cooperative advantage objective. We formulate needs for future research to further elaborate on the learning principles associated with business transformation and suggest implications for practice.
Keywords: 330; business transformation; organizational change; resource-based view; sustainable development; typology